Solving the stokes problem on a massively parallel computer - Axelsson, O.; Barker, V. A.; Neytcheva, M.; Polman, B. (Mathematical Modelling and Analysis, 2001)
We describe a numerical procedure for solving the stationary two‐dimensional Stokes problem based on piecewise linear finite element approximations for both velocity and pressure, a regularization technique for stability, and a defect‐correction technique for improving accuracy. Eliminating the velocity unknowns from the algebraic system yields a symmetric positive semidefinite system for pressure which is solved by an inner‐outer iteration. The outer iterations consist of the unpreconditioned conjugate gradient method. The inner iterations, each of which corresponds to solving an elliptic boundary value problem for each velocity component, are solved by the conjugate gradient method with a preconditioning based on the algebraic multi‐level iteration (AMLI) technique. The velocity is found from the computed pressure. The method is optimal in the sense that the computational work is proportional to the number of unknowns. Further, it is designed to exploit a massively parallel computer with distributed memory architecture. Numerical experiments on a Cray T3E computer illustrate the parallel performance of the method. Stokso uždavinio sprendimas galingais lygiagrečiaisiais kompiuteriais Santrauka. Aprašomas skaitinis metodas stacionariajam dvimačiam Stokso uždaviniui. Metodas pagrįstas baigtinių elementų aproksimacija greičiui ir slėgiui, stabilumo reguliarizacija ir defektų taisymo metodu, kuris pagerina tikslumą. Eliminuojant nežinomus greičius iš algebrinės lygčių sistemos slėgiui surasti gaunama simetrinė teigiamai pusapibrežtinė sistema, kuri sprendžiama vidinėmis‐išorinėmis iteracijomis. Išorinė iteracija naudoja besąlyginį jungtinių gradientų metodą. Vidinės iteracijos, kurių kiekviena atitinka kraštinio elipsinio uždavinio sprendimą kiekvienai greičio komponentei, naudoja sąlyginį jungtinių gradientų metodą. Žinant slėgį surandamas greitis. Metodas yra ekonomiškas, nes kompiuterio skaičiavimai proporcingi nežinomųjų skaičiui. Metodas pritaikytas išnaudoti galingų lygiagrečiųjų kompiuterių su paskirstyta atmintimi architektūrą. Skaitiniai eksperimentai kompiuteriu Cray T3E iliustruoja metodo išlygiagretinimą. First Published Online: 14 Oct 2010